(untitled) (American Journal of Aquaculture and Animal Science, 2023)
Zoonotic diseases cause mild-to-severe illnesses in humans that transmitted from vertebrate animals. The majority of the human diseases originate from animals (61%), and 70% of them are emerging diseases. This study was conducted with the main objective of public health awareness of Zoonotic diseases in Benadir region. Questionnaire was structured into 4 sections namely, socio- demographic characteristics of residents, awareness on domestic animals, wild animals transmission of zoonotic diseases and Zoonotic diseases you heard. Simple random sampling with a total of 80 questionnaires were administered and descriptive statistics was used to analyzed data. The 56 respondents (70%) had domestic animals at home while 27 (33.75%) caged their domestic animals and 36 (45%) respondents vaccinated their domestic animals. The 59 respondents (73.75%) were aware of that the domestic animals (dog, cat, bird, rabbit, goat and cattle) can transmit disease to human. Resident awareness on wild animals’ Zoonosis, showed that 36 (45%) respondents were known of wild animals, while 11 respondents (13.75%) caged their wild animals (Monkey). The 49 respondents (61.25%) were conscious about the transmission of disease to human. Result revealed that the study areas were well aware of zoonotic diseases from both domestic and wild animals. List of Zoonotic diseases that respondents heard were tuberculosis (25%), brucellosis (22.54%), anthrax (17.5%), rabies (20%) and toxoplasmosis (15%). Therefore, we recommend that the people should try the best way to avoid diseases acquired from contact with animals is to thoroughly wash hands with soap and water after close contact with animals can be supervised among adult and young to avoid zoonosis diseases in human. Animal owners must carefully practice biosecurity measures to keep away from diseases contamination both in the animals and human.